FRI0310 Is ultrasonography of salivary gland a validate tool in sjögren syndrome?-study 1: interobserver reliability. (23rd January 2014) - Jousse-Joulin, S.; Jonsson, M. V.; Theander, E.; Milic, V.; Plagou, A.; Luciano, N.; Pascale, R.; Baldini, C.; Bootsma, H.; Tzoufias, A. G.; Bombardieri, S.; Bowman, S.; et al.
Abstract : Background: Ultrasonography (US) of salivary glands is a relatively new test to diagnose primary Sjögren syndrome (pSS) 1 -2 . In 2012, an international group of interest was formed to address the metric qualities of US as a potential outcome measure. A preliminary systematic review highlighted the deficiencies, particularly with regard to the reliability of interpreting and acquiring images and to delineate which abnormalities should be scored. Objectives: The purpose of this study group is to improve reliability and to evaluate several US abnormalities in salivary gland in pSS. Methods: We report here the first part of the study by the group that was conducted in Washington in November 2012. The first meeting bring together an international group of 7 experts in ultrasongraphy of the salivary gland in pSS and aims were 2-fold: first, to assess the interobserver reliability among experts, and second to better define salivary gland abnormalities. 28 scanned images of parotid and submandibular glands were scored. In order to appreciate in everyday practice how the differents sonographers scored, we suggested a simplified scoring as: - Identify the echogeneicity of the parenchyma according to the thyroid parenchyma. - Evaluate the homogeneity of the parenchyma in 3 grades: Grade 0: normal parenchyma, Grade 1: mild heterogeneity, grade 2: severe heterogeneity. We didn't assess the glands size neither the vascularisation because few of the experts use it. Data were analysed using SPSS v15.0 (SPSS Inc., Chicago, IL, USA). Interobserver agreement was estimated using the Cohen's kappa. Coefficient. Agreement among criteria and considered as follows: excellent ≥ 0.80; good, 0.60-0.79; moderate, 0.40-0.59; and poor, < 0.40 Results: Concerning echogenicity the mean kappa was low: 0.3 (0.12-0.8). For homogenicity the mean kappa were respectively: 0.6 (range:0.4-0.8) ; 0.4 (range: -0.1-0.7) and 0.6 (range : 0.5-0.9) for grade 1, 2 and 3. The low agreement for echogeneicity could be due to the evaluation of static images. New definition of each abnormality was elaborated by the experts. In the absence of previous training session a relative good agreement was found between ultrasonographers. Grade 3 is related to the diagnosis of pSS. Conclusions: In the absence of well defined consensus, ultrasonography has an acceptable agreement for homogenicity of the parenchyma but not for echogenicity. However, the homogenicity ccomponent is of true diagnostic value in pSS. Training sessions are required and further studies will assess the scoring system and the value of US in clinical trials fro pSS. References: De Vita S, Lorenzon G, Rossi G et al. Clin Exp Rhumatol, 1992, 10 (4):351-6 Cornec D, Jousse-Joulin S, Pers JO et al. Arthritis Rheum. 2013 Jan;65(1):216-25 Milic VD, Petrovic RR, Boricic IV et al. J Rheumatol. 2009 Jul; 36(7):1495-500 Luciano N, Baldini C, R Pascale et al. Annals of rheum dis. 2012 June S 3 : 16, 302 Theander E et al Annals of rheum dis. 2012 June S 3 : 16, 904 Disclosure of Interest : None Declared